Medieval warfare - Rogers, Clifford J., author. Link
1 online resource.
Keywords: "This volume explores the topics of military revolutions, strategy, and tactics both separately and as they relate to each other. It makes important contributions to understanding European warfare in the Early, High, and especially the Late Middle Ages, as well the military transition to the Early Modern Period. Readers will find detailed analysis of how technological and non-technological developments interacted to effect major changes in how wars were fought across the period. The evolution and capabilities of the English longbow and of early gunpowder artillery are examined in depth. Changes in the tools of war naturally affected plans to employ those tools to achieve political ends--military strategy--but strategy was never dictated by technology. That point is illustrated by examinations of English efforts to conquer Wales; the Anglo-Burgundian alliance of the late Hundred Years War; and the economic factors shaping medieval conquests in general. The nine studies in the volume have all been published previously, but a new introduction shows how they fit together, particularly explaining how they collectively rebut common critiques of Rogers's controversial thesis that European warfare was reshaped by the Infantry and Artillery Revolutions during the era of the Hundred Years' War. Two of the chapters have been substantially expanded, so that the versions printed here should be the ones consulted and cited in the future by scholars of medieval warfare and military revolutions"--